Digital Transformation and Social Capital: Strategies for Traditional Retailers Facing Modern Competition in Palembang - Yeri Resika; Melinda Febrianti (Journal Of Economic Cluster, 2025)
The objective of this study is to examine the business development strategy of "Toko Bambang," a traditional retail business focused on providing community staple goods (sembako). Amidst the rapid expansion of modern retail and digital platforms, traditional grocery stores are compelled to adapt to remain competitive. This study employs a qualitative descriptive approach combined with the SWOT framework. The findings indicate that Toko Bambang possesses significant strengths in social capital, including customer trust, personalized service, and competitive pricing derived from direct sourcing from farmers. However, primary weaknesses lie in the low adoption of digital technology for financial bookkeeping and inventory management, alongside a high dependency on the owner. Significant opportunities are identified in leveraging digital ecosystems and delivery services, while the main threats arise from modern retail competition offering greater convenience. This study concludes by recommending a measurable digital transformation strategy and operational systematization to mitigate the risks associated with manual management. By integrating traditional values of trust with technological efficiency, Toko Bambang can enhance its business resilience and long-term competitiveness.